2010
DOI: 10.1016/j.nbd.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila vesicular monoamine transporter reduces pesticide-induced loss of dopaminergic neurons

Abstract: Dopamine is cytotoxic and may play a role in the development of Parkinson's disease. However, its interaction with environmental risk factors such as pesticides remains poorly understood. The vesicular monoamine transporter (VMAT) regulates intracellular dopamine content, and we have tested the neuroprotective effects of VMAT in vivo using the model organism Drosophila melanogaster. We find that Drosophila VMAT (dVMAT) mutants contain fewer dopaminergic neurons than wild type, consistent with a developmental e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 89 publications
(165 reference statements)
4
67
0
Order By: Relevance
“…5B). This finding is similar to those of Lawal and coworkers (39), who found that overexpression of VMAT in Drosophila protected against the toxicity of a variety of pesticides linked to PD. HPLC analysis of transgenic TH-GAL4; UAS-dVMAT flies (i.e., those where VMAT was overexpressed in DA neurons) showed restoration of DA and DOPAC levels (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5B). This finding is similar to those of Lawal and coworkers (39), who found that overexpression of VMAT in Drosophila protected against the toxicity of a variety of pesticides linked to PD. HPLC analysis of transgenic TH-GAL4; UAS-dVMAT flies (i.e., those where VMAT was overexpressed in DA neurons) showed restoration of DA and DOPAC levels (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, we previously found that an increase in reactive oxygen species is observed in head extracts from 1-octen-3-ol-exposed flies (16). Previous studies modeling Parkinson disease in Drosophila demonstrated that overexpression of the vesicular monoamine transporter promotes packaging of dopamine into vesicles, thereby lowering its cytoplasmic concentrations (19,39). Human genetic studies have found that single nucleotide polymorphisms (SNPs) within the promoter region of VMAT2, in particular gain-of-function haplotypes, are also associated with decreased risk of PD in women (40).…”
Section: Discussionmentioning
confidence: 95%
“…5). This enhanced transmitter release and locomotion suggest elevated dopamine neurotransmission in these mice, a finding reflected in previous work on the overexpression of the Drosophila vesicular monoamine transporter (DVMAT-A) (31)(32)(33). Together with previous findings demonstrating reduced dopamine release and locomotion in VMAT2-deficient animals, the results from the VMAT2-HI mice suggest that there is a gene dosage-dependent regulation of vesicular capacity and dopamine output (21,41,42).…”
Section: Vmat2 Overexpression Increases Dopamine Release and Neurotrasupporting
confidence: 67%
“…Although the detrimental effects of reduced VMAT2 function are recognized, our understanding of the potential benefits of increased VMAT2 function in vivo has been limited to a Drosophila model (31)(32)(33). Thus, we generated VMAT2-overexpressing mice using a bacterial artificial chromosome (BAC) to determine whether increased vesicular packaging could provide an elevation of monoamine output in a mammalian system.…”
mentioning
confidence: 99%
“…This early dysregulation could contribute to the later demise of the neurons, as dopamine has repeatedly shown to be toxic when it escapes normal regulatory mechanisms [43,44]. In support of this hypothesis, polymorphisms in genes involved in dopamine regulation, such as the vesicular and cytoplasmic dopamine transporters have been associated with changes in PD risk in humans and modulation of toxicity to dopamine neurons in experimental models [45,46], and lack of the vesicular transporter induces a loss of dopaminergic neurons in mice [47].…”
Section: Loss Of Striatal Dopamine Is Preceded By Increased Extracellmentioning
confidence: 95%